2015
DOI: 10.1007/s40520-015-0461-x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in leg muscle activity and body sway between elderly adults able and unable to maintain one-leg stance for 1 min: the effect of hand support

Abstract: These results highlight the need to differentiate between patients able and unable to perform OLS unaided for training because of differences in leg muscle activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Moreover, while it seems that reliability is moderate to good for timing OLS studies,46 it is possible that in a clinical setting with older participants timing measurements tend to be less reproducible due to high intraparticipant and interobserver variation, potentially limiting the validity of the OLS results. Additionally, there are distinct ways in which OLS has been assessed, with variations in arm/hand positions, whether arm movements for stabilisation are allowed and position of the opposite leg and foot, with some of the studies allowing a swing leg that incorporates a muscle strength component 18 38 47–49…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, while it seems that reliability is moderate to good for timing OLS studies,46 it is possible that in a clinical setting with older participants timing measurements tend to be less reproducible due to high intraparticipant and interobserver variation, potentially limiting the validity of the OLS results. Additionally, there are distinct ways in which OLS has been assessed, with variations in arm/hand positions, whether arm movements for stabilisation are allowed and position of the opposite leg and foot, with some of the studies allowing a swing leg that incorporates a muscle strength component 18 38 47–49…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that sEMG was able to accurately measure muscle activity through bioelectrical changes [50, 51, 52]. TA played an important role in the stabilization of OLS [53], and the stability of the sEMG signal amplitude during the process of maintaining balance meant the improvement of balance efficiency. So, the mechanism was using less muscle activation to accomplish the same task [54].…”
Section: Discussionmentioning
confidence: 99%